Eliminasi Teori Pembagian Kekuasaan dan Lahirnya Hak Veto Pasca Amandemn Undang-Undang Dasar 1945 - Tekege, Petrus (Universitas Ekasakti, 2023)
If we glance at the theory Montesqeuie Trias Politica, the Act established powers that be in the hands of the legislature. Delivery is based on fhilosophy that the legislature is an institution in which representatives of the people of Oran is a collection of those options that carry out the mandate of the people who choose it. While eksekutuf as the executor of what the will of the people under the law of products made by legislatures. Power to form the Law in Indonesia after the 1945 amandemn reflect Montesqeuie theory but not entirely in the hands of the legislature can be said even with the power between the parliament and the president which, according to opinion of the writer is still to be debated again in the future.